Cogeneration and trigeneration applications - Öztop, Hakan Fehmi; Hepbasli, A (Taylor & Francis Inc, 2006)
Combined heat and power cogeneration, or autoproduction as it is known in Turkey, is the simultaneous production of heat and electricity, while trigeneration includes the cold production in addition to cogeneration. This technology has been advanced by governmental support and the continuing need for additional electricity generation within Turkey. The present study deals with cogeneration and trigeneration applications in Turkey, giving the electricity market development. Only four cogeneration plants with a total capacity of 30 MWe were operated up to 1994, while trigeneration applications have started for the last two years. The total installed cogeneration capacity is expected to reach up to 6,000 MWe by 2005, which would represent about 20% of Turkey's total installed electricity generating capacity. In this context, cogeneration and trigeneration have had, or will have, a significant and increasing role in dictating the energy strategies for Turkey.
Keywords: cogeneration; combined heat and power; CHP; trigeneration; electricity market; Turkey